Spatial perspectives in the exploitation of the wind resource in ciudad Ixtepec, Oaxaca - Sánchez Casanova, Wendy Marilú (Agricultura, Sociedad y Desarrollo, 2020)
The study of spatial representations is of widely used in social sciences, since it strengthens critical aspects about the nature-society relationship such as political ecology. Thus, this study identifies and analyzes the categories of space, landscape, territory, place and region facing the imminence of the exploitation of wind energy in Ciudad Ixtepec, Oaxaca, through a qualitative approach, highlighting the perspective from the actor, supported by triangulation and semi-structured interviews. It was found that the category of territory predominates through two forms of appropriation, one by the government and by private wind companies, which hold the category of territory in its political-legal sense, based on a connection between landscape and region with classificatory and economic aims. On the other hand, the Ixtepec comuneros (communal co-proprietors), who have the Yansa Foundation as possible partner and mediator, appeal to the history and experience, reclaiming their right to be their own agents in their territory with connection with the category of place, with landscape being a perspective that contributes to the scheme of attachment and rootedness of the space in controversy.